Perkembangan Kognitif Tercapai pada Anak Sekolah Dasar MIN 1 Bantul Yogyakarta - Yeni Wulandari Baiq Arnika Saaadati Suyadi (Al-Riwayah : Jurnal Kependidikan, 2019)
The purpose of this study was to determine the cognitive development achieved in grade IV elementary school (SD/MI) children at the State 1 Madrasah in Bantul, Yogyakarta. The form of research used is qualitative research. The results showed that the cognitive development of children in grade IV of elementary school was in the concrete operational stage (10 years). At this stage, the child has begun to be able to think logically, rationally and objectively, but towards concrete objects. In addition, in elementary school the cognitive development of children is at the stage of thinking, such as the ability to remember, reason, beride, imagine and creativity. Then also can imagine by making works such as poetry and poems. Children who have cognitive development have high levels of intelligence. This evidenced from reports on student learning outcomes from grades I-IV. Also has a good focus and activity during the learning process.Based on the results of interviews with the children studied, it turns out that children who have achieved cognitive development can provide answers related to their dreams in the future. As for the things that support cognitive development achieved by children are genetic and environmental factors.The results showed that these two factors greatly influenced the cognitive development of children. The child studied by the researcher turned out to be one of the children whose parents were one of the lecturers and caregivers of the Islamic boarding school.In addition, the environmental influence of peers and the home environment is very influential. The children studied always study together with children who are in boarding schools. Besides that, he also often invited by his parents to perform poetry at an Islamic cafe in Yogyakarta